(untitled) (Journal of the Medical College for Women & Hospital, 2026)
Background: Polycystic ovarian syndrome (PCOS) is a common endocrine disorder among women of reproductive age, often associated with psychological comorbidities such as depression.Aim: To determine the prevalence of depression and identify its associated determinants among women diagnosed with PCOS. Materials and Method: A hospital-based cross-sectional study was conducted at the Outpatient Departments of Obstetrics and Gynecology and Reproductive Endocrinology and Infertility of Bangladesh Medical University from January 2023 to December 2023. Women of reproductive age with a confirmed diagnosis of PCOS based on the Rotterdam criteria were included. Data were collected through face-to-face interviews using a semi-structured questionnaire, and depression was assessed using the PHQ-9.Results: A total of 95 women with PCOS participated. Most were aged 26–35 years, married, Muslim, and homemakers. The majority had secondary or higher education, no children, and belonged to middle-income households. Menstrual irregularity was reported by 54.7% of participants, and 38.9% were overweight or obese. Depression was highly prevalent, with 45.3% experiencing mild depression, 40.0% moderate, 13.7% moderately severe, and 1.1% severe. Significant determinants of depression included religion (p=0.04), occupation (p=0.03), age at menarche (p=0.02), menstrual cycle pattern (p=0.03), use of birth control methods (p=0.02), BMI (p=0.02), physical inactivity (p=0.04), and skipping meals (p=0.05). No significant association was found with age, marital status, education, or smoking habit.Conclusion: Depression is highly prevalent among women with PCOS in Bangladesh. Reproductive factors, lifestyle behaviors, and occupational status significantly influence depression severity. J Med Coll Women Hosp.2026; 22(1): 124-136